Um estudo sobre mapeamento de produtos do agronegócio com potencial para a proteção por Indicação Geográfica : o caso da laranja produzida no território sul sergipano - Santos, Adeilson Freire dos (2015)
Geographical Indication (GI) has been considered a market strategic tool for commercial organizations worldwide, bringing differentiation of products and services in relation to competition, in a context of greater demand from consumers who are willing to acquire them for uniqueness, tradition and guarantee local production. The Brazilian Industrial Property Law establishes that the GI is classified into two modalities: Indication of Origin (IO) and Designation of Origin (DO). Several studies have been performed on GI in Brazil and around the world describing concepts, applications and case studies of GI, emphasizing the development and appreciation of regions after getting her record of producing areas by IO or DO. But when it comes to mapping potential future products for GI in sectors of great importance for the Brazilian economy, such as agribusiness, it is observed that there is a gap in this type of study in the state of Sergipe, even with the work of the Ministry of Agriculture, Livestock and Supply at the national level. Whereas orange produced in the South Territory of Sergipe is an important product in the state´s economy and it is representative on the national scene, this study aims to identify the potential that the orange produced in this region has to be protected by GI. This research is characterized as a qualitative exploratory case study. To achieve the goals and respond the research questions, data were collected through bibliographic research, documents and interviews with five (5) citrus industry experts of South Sergipe. These data were analyzed and classified into categories for content analysis. The study concludes and presents elements that suggest that South Orange Sergipe is a product with potential for GI because it has history and culture linked to the territory, it is known and marketed in the state and beyond, which can configure an IO, and it also has different taste qualities, because it is grown in a region with unique climate, soil and temperature, according to experts, which could set up a DO. This region of unique features extends to some of Bahia Northeastern cities. The study also shows a map with the planting areas with potential for demarcation of the GI. The implementation of a GI in South Sergipe can be a way for the resumption of growth and development of citrus production in the region by organizing producers to achieve registration at the INPI and improving business management. However, this can only occur if producers are united and committed to the GI and relying on the commitment of Federal, State and Municipal government and institutions connected with them such as MAPA, Embrapa, Emdagro, Sebrae and support of the University.